2015
DOI: 10.1152/jn.00012.2015
|View full text |Cite
|
Sign up to set email alerts
|

D1 and D2 antagonists reverse the effects of appetite suppressants on weight loss, food intake, locomotion, and rebalance spiking inhibition in the rat NAc shell

Abstract: R. D1 and D2 antagonists reverse the effects of appetite suppressants on weight loss, food intake, locomotion, and rebalance spiking inhibition in the rat NAc shell. J Neurophysiol 114: 585-607, 2015. First published May 13, 2015 doi:10.1152/jn.00012.2015.-Obesity is a worldwide health problem that has reached epidemic proportions. To ameliorate this problem, one approach is the use of appetite suppressants. These compounds are frequently amphetamine congeners such as diethylpropion (DEP), phentermine (PHEN),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
50
2

Year Published

2018
2018
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 84 publications
4
50
2
Order By: Relevance
“…In this study, diethylpropion showed mild piloerection and hyperactivity between 10 and 30 mg/kg, meanwhile topiramate induced mild sedation between 300 and 560 mg/kg. The observed safety profiles agree with previous studies where diethylpropion induces motor stimulation (Kalyanasundar et al, ; Safta et al, ; Samanin & Garattini, ) and topiramate decreases anxiety (Abo‐Elmatty & Zaitone, ) are the main side effects in rat. Oral co‐administration of diethylpropion + topiramate only induced mild piloerection and hyperactivity at the highest tested dose at 1:1 and 3:1, but not 1:3, dose ratios, respectively.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…In this study, diethylpropion showed mild piloerection and hyperactivity between 10 and 30 mg/kg, meanwhile topiramate induced mild sedation between 300 and 560 mg/kg. The observed safety profiles agree with previous studies where diethylpropion induces motor stimulation (Kalyanasundar et al, ; Safta et al, ; Samanin & Garattini, ) and topiramate decreases anxiety (Abo‐Elmatty & Zaitone, ) are the main side effects in rat. Oral co‐administration of diethylpropion + topiramate only induced mild piloerection and hyperactivity at the highest tested dose at 1:1 and 3:1, but not 1:3, dose ratios, respectively.…”
Section: Discussionsupporting
confidence: 90%
“…The ED 30 value of diethylpropion in 12 hr‐food deprived rats was slightly lower, but not significant, than the ED 30 value in of nondeprived rats. Kalyanasundar et al () reported that diethylpropion produces a greater weight loss, with less tolerance and\rebound weight gain when is administered in conjunction with high fat dietary restriction and during the active phase of the day a phenomenon that id related to dopaminergic systems (Kalyanasundar et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations